Vplyv polychlórovaných bifenylov (PCB) na aktivitu pecenovej anilínhydroxylázy a na niektoré metabolické parametre krvi prasiat - Guoth, J; Kacmár, P; Teleha, M; Vasil', M (Veterinarni medicina, 1984)
For 70 days two groups of 10-week gilts were given feed supplemented with PCB commercial mixture of Czechoslovak make (Delor 105), at the doses of 10 and 50 mg. .kg-1 of feed. Over the experimental period, animals were administered 1000 mg or 5000 mg of PCB mixture. During the experimental period the levels of glucose, cholesterol, urea, total protein, vitamin A, calcium, inorganic phosphorus and the activities of AF, ALT and AST enzymes were determined twice. At the end of this experiment the aniline hydroxylase activity in microsomal fractions of liver was determined and pronounced induction effect of PCB on the enzymatic system was observed. Out of the studied metabolic parameters of blood plasma, the decrease in vitamin A level was significant.
Keywords: Female; aromatické hydroxylasy; anilinhydroxylasa; Swine; Animals; Aryl Hydrocarbon Hydroxylases; ženské pohlaví; Aniline Hydroxylase; játra; zvířata; Liver; Polychlorinated Biphenyls; polychlorované bifenyly; prasata